Accident of fate : a personal account, 1938-1945 - Rochlitz, Imre, 1925- (Life writing series., 2011)
Offers an account of persecution, rescue, and resistance in the Axis-occupied former Yugoslavia. This book helps to clarify and render accessible the complexities and contradictions of conflict and genocide in wartime Yugoslavia.